2016
DOI: 10.1021/acs.joc.6b02108
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Catalyzed Synthesis of Diaryl Selenides by Reaction of Diaryl Diselenides with Aryl Boronic Acids

Abstract: We described herein our results on the silver-catalyzed synthesis of diaryl selenides via a cross-coupling reaction of diaryl diselenides with aryl boronic acids. The methodology is tolerant to electron-donor and electron-withdrawing groups at the substrates and the desired products were obtained in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…Both anomers of the C1 stannanes can be prepared by straightforward manipulations of glycal substrates, affording 1,2‐ cis ‐ and 1,2‐ trans isomers, and both anomers of the 2‐deoxysugars . Methods that promote the formation of C(sp 2 )−Se bonds are well‐established using Ag, Cu, Fe, Ni, and Pd complexes and provide precedent for the reasonable extension of these technologies to the stereoselective synthesis of C(sp 3 )−Se bonds. Investigation into this approach presents an opportunity to fill the knowledge gaps within this underdeveloped area in glycoside synthesis …”
Section: Figurementioning
confidence: 99%
“…Both anomers of the C1 stannanes can be prepared by straightforward manipulations of glycal substrates, affording 1,2‐ cis ‐ and 1,2‐ trans isomers, and both anomers of the 2‐deoxysugars . Methods that promote the formation of C(sp 2 )−Se bonds are well‐established using Ag, Cu, Fe, Ni, and Pd complexes and provide precedent for the reasonable extension of these technologies to the stereoselective synthesis of C(sp 3 )−Se bonds. Investigation into this approach presents an opportunity to fill the knowledge gaps within this underdeveloped area in glycoside synthesis …”
Section: Figurementioning
confidence: 99%
“…Synthesis of heterocyclic chalcogenic molecules is a topic of great challenge among the synthetic organic community. Most reported transformations involve the nucleophilic substitution of 2‐halopyridines with salts of selenols or transition metal catalyzed cross‐coupling reactions of diselenides with aryl boronic acids (Scheme a) or 2‐halopyridines (Scheme b). In addition, Alves et al have reported the synthesis of these moieties via the reaction of 2‐halopyridines with diselenides using glycerol as solvent and hypophosphorus acid as the reducing agent (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
“…Since their reports, modern studies have been described to improve this kind of transformation. In particular, metals have been efficiently applied as catalysts for the cross-coupling of diorganyl chalcogenides with boronic acids, for instance, employing indium [ 47 ], iron [ 48 ], copper [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ] and silver [ 56 ].…”
Section: Introductionmentioning
confidence: 99%